Termite taxonomy from 2001–2021: the contribution of Zootaxa - Constantino, Reginaldo (Zootaxa, 2021)
Termites comprise a relatively small group of insects, with 3176 known species (2976 living and 200 fossil) (Constantino 2020).  They include, however, very important urban and agricultural pests, and also major decomposers of plant matter in terrestrial ecosystems, especially in the tropics.  For instance, the annual economic impact of a single invasive termite species, Coptotermes formosanus, was estimated as US$11 billion in the United States in 1999 (Su 2002), placing it among the most important insect pests in the world.